Optimization of Ultrasound-Assisted Extraction of Phloretin and Other Phenolic Compounds from Apple Tree Leaves (Malus domestica Borkh.) and Comparison of Different Cultivars from Estonia - Sana Ben-Othman; Hedi Kaldmäe; Reelika Rätsep; Uko Bleive; Alar Aluvee; Toonika Rinken (MDPI AG, 2021)
Polyphenolic compounds, plant secondary metabolites essential for plant survival, are known for their high antioxidant and anti-inflammatory activity. In addition, several polyphenols, such as phloretin, also have potential antiviral effects, making these compounds potential ingredients of biofunctional foods. A promising source for the extraction of phloretin is a by-product of apple production-apple tree leaves. Focusing on green technologies, the first aim of the present study was to optimize the direct ultrasound-assisted extraction conditions to gain the maximum yield of phloretin from air-dried apple leaves. For the optimization of process parameters, we applied the response surface method with Box-Behnken design. The optimal extraction conditions were extraction time 14.4 min, sonication amplitude 10% and 10 g of sample per 100 mL solvent (70% ethanol, w/w). Using these conditions, we assessed the content of individual and total polyphenolic compounds along with antioxidant activity in the leaves of different autumn and winter apple cultivars grown in Estonia. The analyses were carried out with chromatographic (HPLC-DAD-MS/MS) and spectrophotometric methods. The phloretin concentration ranged from 292 to 726 µg/g and antioxidant activity from 6.06 to 11.42 mg GA eq./g, these being the highest in the local winter cultivars 'Paide taliõun' and 'Tellissaare', respectively.